A two-year retrospective survey of drowning deaths in the state of Goa - Sreekumar, Bharat; Suares, Sheryl; Kumar, Pannag S; Victor Fernandes, Andre (Journal of Indian Academy of Forensic Medicine, 2021)
A two year retrospective survey was conducted spanning from 2017-2018 in the Department of Forensic Medicine and Toxicology on cases brought for postmortem as deaths due to drowning. A total of 220 cases of drowning in the state of Goa have been categorically analyzed and presented based on age, sex, fresh water or salt water drowning and the manner of death.The most common source of fresh water drowning was found to be rivers (40%). The study showed that accidental drowning (73.08%) was more common than suicidal (26.37%) and homicidal (1%) drowning. Highest number of deaths was recorded in the age group of 31-45 years, with higher male preponderance.